Impact of Green Fiscal Policy on Investment Efficiency of Renewable Energy Enterprises in Kazakhstan - Mazina, Ainur; Syzdykova, Dinara; Myrzhykbayeva, Ainur; Raikhanova, Gulnur; Nurgaliyeva, Aliya (International Journal of Energy Economics and Policy, 2022)
Years of industrialization and reliance on energies such as oil and coal have resulted in global pollution on an unprecedented scale. Carbon footprint, destruction of forests, melting away of ice caps in the North Pole, and climate change have persuaded many to adopt a more sustainable growth. In the wake of this catastrophe, “green” energy is a phenomenon that takes a step toward sustained development. Green energy consists of innovative and cost-effective ways to address the global consciousness by switching to renewable energy, water resources management, waste reduction, etc. Green Fiscal Policy aims to align prices and mobilize resources for climate change and sustainable development. Many developed and developing countries like Kazakhstan are taking the initiative towards zero carbon emission and renewable energy. The challenges of implementing the required policies include overcoming the barriers of the status quo to establish a new Geo-political and economic system in Kazakhstan. Political and economic challenges persist despite its vision for 2050 that Green Economy influences. This report focuses on Kazakhstan’s natural resources, topography, and renewable energy enterprises. The Green Fiscal Policy is closely examined over Kazakhstan’s current investment efficiency scenario.